Microstructure and Electrical Properties of (K0.48Na0.52)NbO3 – (0.16/5.15)K2.9Li1.95Nb5.15O15.3 Lead-Free Piezoceramics Prepared by Two-Step Sintering Method. Issue 1 (2nd January 2016) - Yang, Jie; Zhang, Zhiqiang; Yang, Qunbao; Li, Yongxiang
Abstract : The phase structures, microstructures and electrical properties of (K0.48 Na0.52 )NbO3 –(0.16/5.15)K2.9 Li1.95 Nb5.15 O15.3 prepared by conventional method (CM) and two-step sintering method (TS) were studied. All the ceramics show typical tetragonal structure at room temperature. The average grain size of the ceramics sintered by CM is about 20 μm. However, it can be decreased to 1–3 μm by TS, which can provide a large driving force for crystal growth through solid-state crystal growth method (SSCG). Prolonging sintering time will not change the dielectric and ferroelectric properties. Therefore, TS is a promising way to prepare matrix for growing single crystal with chemical homogeneity by SSCG.